2013
DOI: 10.1021/ol402713g
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Practical Synthesis of Anthracenes through Gold-Catalyzed Cyclization of o-Alkynyldiarylmethanes

Abstract: A concise gold-catalyzed method for the preparation of anthracenes from o-alkynyldiarylmethanes has been developed. Under mild reaction conditions, versatile anthracene derivatives were formed in moderate to good yields. The high flexibility, broad substrate scope, and mild nature of this reaction render it a viable alternative for the synthesis of anthracenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 86 publications
3
20
0
Order By: Relevance
“…These results indicated that path a should be the main pathway of the reaction, although the formation of intermediate A could not be detected by monitoring the cyclization reaction by 1 H NMR spectroscopy under the optimized reaction conditions (Table 1, entry 8). Notably, similar to our previously reported results,9a part of 2 a might be generated via path b involving a gold‐catalyzed hydration and subsequent acid‐catalyzed cyclodehydration (Table 4, entries 2–3), which may also explain the role of acid here to accelerate the minor pathway.…”
Section: Methodssupporting
confidence: 88%
See 3 more Smart Citations
“…These results indicated that path a should be the main pathway of the reaction, although the formation of intermediate A could not be detected by monitoring the cyclization reaction by 1 H NMR spectroscopy under the optimized reaction conditions (Table 1, entry 8). Notably, similar to our previously reported results,9a part of 2 a might be generated via path b involving a gold‐catalyzed hydration and subsequent acid‐catalyzed cyclodehydration (Table 4, entries 2–3), which may also explain the role of acid here to accelerate the minor pathway.…”
Section: Methodssupporting
confidence: 88%
“…Next, a variety of gold catalysts were investigated (Table 1, entries 1–9), and [(C 6 F 5 ) 3 PAuNTf 2 ] was found to be the best among them (Table 1, entry 8). Notably, similar to our previously reported protocol,9a the main byproduct here was methyl ketone 3 a formed by a gold‐catalyzed hydration reaction. In addition, PtCl 2 and AgNTf 2 only led to poor results (Table 1, entries 10–11).…”
Section: Methodssupporting
confidence: 71%
See 2 more Smart Citations
“…In recent years, the Lewis acid/Brønsted acid mediated domino reaction has been successfully applied for the synthesis of a wide variety of π‐conjugated heterocycles 15. Shu et al reported16 the synthesis of substituted anthracenes by gold‐catalyzed intramolecular cyclization of orthoalkynyl‐diarylmethanes. Matsuo and co‐workers achieved17 the synthesis of anthracenes from diarylmethanes through a Bradsher‐type reaction that involved formylation of the aryl unit followed by Lewis acid catalyzed Friedel–Crafts intramolecular cyclization reaction.…”
Section: Introductionmentioning
confidence: 99%